La violencia intrafamiliar y su incidencia en el proceso de enseñanza aprendizaje en los niños de educación básica elemental, periodo 2016-2017 - Comina Caisaguano, Elvia Judith (2017)
The present research aimed to determine the causes that affect intrafamily violence in the teaching-learning process at Aurelio Dávila Cajas school in Zumbahua Parish,Pujilí Canton. Domestic violence is a social problem that mainly affects children, adolescents and women without taking into account the social or cultural level. The applied methodology was the exploratory and descriptive research, while for the design, it was applied non-experimental research supported by the bibliographical and field or quantitative, as well as the techniques of observation and the application of instruments such as the surveys and the interview. They helped to verify and check the expected results. The impact that this work had is a psychological novelty since it is unique and was carried out for the first time in Zumbahua Parish. It was determined that the intrafamily violence afects the teaching learning process because they are thinking in the problems and they do not pay attention in classes. This afected the academic perfomance in the institution Basic Educatio. Among the main beneficiaries of the investigative work were the children of the "Aurelio Dávila Cajas" school and the parents as well as the intra-family relationship, and thus the teaching-learning process.